COVID-19 Among Patients With Inflammatory Rheumatic Diseases - Esatoglu, Sinem Nihal; Tascilar, Koray; Babaoğlu, Hakan; Bes, Cemal; Yurttas, Berna; Akar, Servet; Pehlivan, Ozlem; Akleylek, Cansu; Tecer, Duygu; Seyahi, Emire; Yuce-Inel, Tuba; Alpay-Kanitez, Nilufer; et al. (Frontiers in Immunology, 2021)
Background: The course of novel coronavirus disease 2019 (COVID-19) has been of special concern in patients with inflammatory rheumatic diseases (IRDs) due to the immune dysregulation that may be associated with these diseases and the medications used for IRDs, that may affect innate immune responses. Objective: In this cohort study, we aimed to report the disease characteristics and variables associated with COVID-19 outcome among Turkish patients with IRDs. Methods: Between April and June, 2020, 167 adult IRD patients with COVID-19 were registered from 31 centers in 14 cities in Turkey. Disease outcome was classified in 4 categories; (i) outpatient management, (ii) hospitalization without oxygen requirement, (iii) hospitalization with oxygen requirement, and (iv) intensive care unit (ICU) admission or death. Multivariable ordinal logistic regression analysis was conducted to determine variables associated with a worse outcome. Results: 165 patients (mean age: 50 ± 15.6 years, 58.2% female) were included. Twenty-four patients (14.5%) recovered under outpatient management, 141 (85.5%) were hospitalized, 49 (30%) required inpatient oxygen support, 22 (13%) were treated in the ICU (17 received invasive mechanic ventilation) and 16 (10%) died. Glucocorticoid use (OR: 4.53, 95%CI 1.65-12.76), chronic kidney disease (OR: 12.8, 95%CI 2.25-103.5), pulmonary disease (OR: 2.66, 95%CI 1.08-6.61) and obesity (OR: 3.7, 95%CI 1.01-13.87) were associated with a worse outcome. Biologic disease-modifying antirheumatic drugs (DMARDs) do not seem to affect COVID-19 outcome while conventional synthetic DMARDs may have a protective effect (OR: 0.36, 95%CI 0.17-0.75). Estimates for the associations between IRD diagnoses and outcome were inconclusive. Conclusions: Among IRD patients with COVID-19, comorbidities and glucocorticoid use were associated with a worse outcome, while biologic DMARDs do not seem to be associated with a worse outcome.